(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
High-riding jugular bulb (HRJB) is an uncommon vascular anomaly of the temporal bone that may pose a significant risk during otologic surgery. Keratosis obturans (KO), characterized by accumulation of desquamated keratin within the external auditory canal, can occasionally coexist with middle ear and temporal bone anomalies, complicating surgical management. We report a rare case of keratosis obturans associated with a high-riding jugular bulb encountered intraoperatively during canal clearance. The patient presented with conductive hearing loss, otalgia, and chronic ear discharge. Routine laboratory investigations were within normal limits. High-resolution computed tomography (HRCT) of the temporal bone showed soft tissue opacification involving the middle ear cavity and mastoid air cells on the right side with hypopneumatization suggestive of otomastoiditis. The left ear demonstrated a small polypoidal mucosal thickening involving the tympanic membrane, likely representing keratosis obturans, without expansion of the bony canal. Imaging also revealed a high-riding jugular bulb. Surgical clearance was performed with meticulous dissection to avoid vascular injury and catastrophic hemorrhage. Histopathological examination confirmed keratosis obturans. Awareness of this anatomical variation and careful preoperative radiological evaluation are essential for safe surgical intervention. This case highlights the importance of recognizing HRJB as a potential surgical hazard in patients with keratosis obturans.¹⁻³